Pengaruh Lingkungan Kerja terhadap Kinerja Karyawan Badan Narkotika Nasional Provinsi Sumatera Utara - Dina Siregar; Juliana Nasution (El-Mujtama: Jurnal Pengabdian Masyarakat, 2022)
An iorganization iis isynonymous iwith iperformance, iwhich iis idefined ias ia imeasure iof iwhere ian iorganization iis isuccess iin iachieving ithe itarget ior inot, iin ithe iprovince iof iNorth iSumatera iBNN iin i2017 iwhose iactivities irealized ionly ireached i54.25%. iOne iof ithe iexternal ifactors ithat ican iinfluence iis ithe iwork ienvironment, iit ishows ithat iBNN iprovince iof iNorth iSumatera ihas ia iworking ienvironment ican icreate ia idisgruntled iemployee.This istudy iwas iconducted ito idetermine ithe ieffect iof ithe iwork ienvironment ion iemployee iperformance. iThe imethod iused iin ithis iresearch iis iquantitative. iUsing imultiple ilinear iregression iwith iSPSS iVer.23 ias idata iprocessing itools. iFrom ithe idata iprocessing ishowed ithe iphysical iwork ienvironment iaffects i33.1% iand inon-physical iwork ienvironment ihas ia igreater iinfluence isecond iknown i43.2% ia isignificant iimpact ion iemployee iperformance. iIt iwas iconcluded ithat ithe ieffect ion ithe iperformance iof iemployees iin ithe iprovince iof iWest iNorth iSumaterais ia inonphysical iwork ienvironment, ibecause iBNN iitself ihas iactivities iassociated iwith ivarious iorganizations ioutside ithe ioffice. Keywords: Physical Work Environment, Non-Physical Work Environment, Employee. Ferformance